(untitled) (KYAMC Journal, 2022)
Background: Major Depressive Disorder (MDD) is a major health problem. In Bangladesh, the prevalence of depressive disorder is 4.1%. MDD is the second cause of disability and therefore, alerts physicians of clinical psychiatry. Antidepressants are the treatment of depression. Administration of zinc indicates an important role in mood and depression. Objective: To investigate the role of zinc in MDD. Materials and Methods: A randomized controlled trial; done in the Department of Pharmacology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from March 2019 to August 2020. Placebo group with SSRI was group ‘A’ (n =35) and zinc supplementation with Selective serotonin reuptake inhibitors (SSRIs) was group ‘B’ (n=38) for 8 weeks. A baseline visit and a follow-up visit were given after 8 weeks. Then; the severity of depression and serum zinc level was assessed. Results: After 8 weeks, the Depression, Anxiety and Stress Scale (DASS-21) score was found 11.77 ± 4.08 SD and 8.53 ± 4.38 SD in placebo and intervention group respectively. Percentage of decreased DASS-21 score was found 37.68 ± 21.47 SD and 54.48 ± 21.94 SD in placebo and intervention groups respectively. The DASS-21 score was statistically significant. The more significant reduction of DASS-21 score after zinc administration. After 8 weeks, serum zinc levels were found 0.69 ± 0.10 SD in the placebo group and 0.78 ± 0.12 SD in the intervention group. The percentage of changes in the serum zinc level in the placebo group was 0.19 ± 16.17 and in the intervention group 5.88 ± 18.39. The serum zinc levels were significant within the intervention groups. The significant elevation of serum zinc levels after 8 weeks of zinc administration in the intervention group. Conclusion: Zinc supplementation along with SSRI in MDD patients significantly ameliorated the severity of depression. KYAMC Journal Vol. 13, No. 01, April 2022: 18-23